ISSUES OF TEACHING FOREIGN LANGUAGES IN PRIMARY CLASSES - Ismailova Shaira Ferdausovna (American Journals, 2023)
This article explores challenges in teaching foreign languages to primary school students. It covers issues such as cognitive development, attention span, teacher preparedness, resources, parental involvement, assessment methods, policy considerations, and cultural sensitivity.
Keywords: teaching, foreign languages, primary classes, challenges, cognitive development, attention span, teacher preparedness, resources, parental involvement, assessment methods, policy issues, cultural sensitivity.